Peers in careers : peer relationships in the transition from school to work - Rüschoff, Britta [Verfasser] (University of Groningen, 2015)
This thesis takes a relational approach to career development and addresses the question "how peer relationships affect young people's career decisions and their career-directed behavior at different stages of the transition from school to work. The central aim of the studies that comprise this book is therefore to shed light on the way in which relationships with peers affect this transition. The first part of this book focuses on young people's career-related cognitions, particularly their work values, and their career-directed behaviors. Work values refer to individuals' conceptions of what rewards of their future jobs are desirable them and serve as indicators of what motivates young people to work, how satisfied they are with their future jobs, and what kinds of work-related aspects are relevant to them when making career decisions. The second part of this book focuses on the developmental implications of the onset of employment and particularly the consequences for individuals' engagement in adverse and norm-breaking behaviors during the school years." (Text extract, BIBB-Doku)
Keywords: P 1.1 Jugendliche; P 1.2 Erwachsene; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; Jugendlicher; Junger Erwachsener; Berufseinmündung; Zweite Schwelle; Berufswahlverhalten; Straffälligkeit; Einflussfaktor; Peer group